Стан регіонарної гемодинаміки у хворих на гіпотиреоз - Зелінська, Н. Б. (Clinical Endocrinology and Endocrine Surgery, 2009)
In the article the results of research of the state of regional hemodynamics are presented from data of rheography in 323 patients with hypothyroidism. We found out such changes of hemodynamics as a decline of circulation of blood; increase of tone of precapillary vessels, and also vessels of middle and large caliber, with predominance of tone of the latter; a decline of tone of the venules is due to worsening of outflow of blood. The increase of tone of vessels, decrease of their elasticity is accompanied with the increase work energy of heart. Correlation of phases of systole of left ventricle changes at hypothyroidism, with predominance of duratoin period of tension of heart for banishing of blood from heart to the main vessels. The pathological changes of indexes of low limb’s rheography take place already on the initial stage of desease.